Learning Management in Innovative Communities for Marketing and Digital Marketing of Agricultural Products: A Case Study of Date Palm Products, Rai Sukjai Project, Ban Hao, Ratchaburi Province - Worapongpat, Ntapat; Chaiwiwat, Uswin; Thavisin, Natthanon; Sun, Qingchao (Journal of Education and Learning Reviews, 2025)
Background and Aim: The agricultural sector in Thailand, particularly date palm cultivation, faces challenges in marketing and distribution. The Rai Sukjai Project in Ban Hao, Ratchaburi Province, aims to address these challenges by integrating innovative community learning management and digital marketing strategies to improve the visibility and sales of date palm products. This study investigates the effectiveness of these strategies and their impact on the community’s economic sustainability. Materials and Methods: This research utilizes a mixed-methods approach, combining quantitative data from surveys of farmers and stakeholders with qualitative interviews and case studies. Digital marketing platforms, community learning sessions, and innovative marketing techniques were assessed for their effectiveness in promoting date palm products. Data were analyzed through statistical tools and content analysis to evaluate the project's outcomes. Results: The results indicate that the integration of digital marketing significantly enhanced product visibility, with online sales increasing by 35% within the first year. The community's engagement in learning sessions improved marketing skills, fostering greater participation in the innovation process. Positive outcomes were observed in both local and national markets, and community members reported increased confidence in using technology for marketing purposes. Conclusion: The Rai Sukjai Project successfully demonstrated that effective learning management combined with digital marketing strategies can significantly improve the marketing and distribution of agricultural products. The study highlights the need for ongoing innovation and digital adaptation in rural communities to sustain agricultural economic growth.